Acesso e utilização dos serviços de saúde da população da etnia Xakriabá, Norte de Minas Gerais - Livia de Souza Pancracio de Errico (2011)
Studies have shown that the determinants of access to health services are directlyrelated to the characteristics of the communities, their social, cultural, and economic status aswell as their geographic location and the spatial distribution of the services. Thus, given itscultural specificity and the particular organization of the health system, indigenouscommunities add new information to support or redefine the group of determinants ofaccessibility to health services. This can positively impact on the remodeling of healthpolicies and health care programs for ethnically differentiated groups. In this sense, the studyaimed to evaluate the access and use of health services by indigenous Xakriabá, residents ofthe Xakriabá Indigenous area, in the northern part of Minas Gerais State in Brazil in relationto the influence of demographic, socioeconomic, and health status factors. Data werecollected from a population sample of 472 Xakriabá, by the application of questionnairesabout the demographic and socioeconomic aspects, as well as the characteristics of access andutilization of primary care and specialized health services. A multivariate model was createdusing Poisson regression, for the three different outcomes: primary health care access,specialized health services access, and health services utilization. . The strength of associationwas measured by Prevalence Ratio (PR) and its 95% confidence intervals (95% CI). Thestatistical significance level was set at 5% (p 0.05). The results showed that the selfassessedhealth status improved both the access and the health services use. The prevalence ofaccess to primary care was higher for females. Social support and participation in communityorganizations are two other factors that enhanced the likelihood of accessing primary care. Areduction in access occurred for individuals living further than five kilometers from the healthcenter. Older persons, age group between 30 and 59 years old, were associated to lowerprevalence rates of access to specialized health services, while for those receiving financialsupport from the government, under the Bolsa Família program, had their access increased by50%. Additionally, as the educational level increased, there was a higher prevalence of the useof health services. The results showed that there are differences in access, susceptible to theeffects of intersectoral actions in the educational and economic spheres, and also in theorganization of public transport service in the reserve area. In addition, health services shouldaddress mens health needs and identify measures to increase services access by olderindividuals. The provision of medical services and nursing care for indigenous people shouldbe thought considering their health beliefs and attitudes, which results from the interactionbetween their self-treatment system and the western medical care.